2014
DOI: 10.1177/2277975214542057
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Analysis of Sustainability Disclosure Practices: Evidence from India and China

Abstract: The present study seeks to access and compare the sustainability reporting practices in two major economies, that is, India and China. Index developed under global reporting initiative (GRI) guidelines is used. Content analysis is employed as a data collection tool. A total of 17 companies from BSE-30 (India) and 19 companies from SSE 50 (China), producing sustainability reports within the time period 2006–2007 to 2010–2011, comprise the sample set. Independent sample t test is used to compare the disclosure p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 29 publications
0
8
0
4
Order By: Relevance
“…The amount and quality of CSD in the developed countries is far better than the developing countries (Bhatia & Tuli, 2014; Wanderley, Lucian, Farache, & de Sousa Filho, 2008). In the race that features two of the fastest emerging economies, India is leading in CSD and China is lagging behind (Baskin, 2006; Bhatia & Tuli, 2014). Bhatia and Tuli (2014) found a significant difference in the extent of CSD between India and China; the total mean disclosure score of India was 81.34 per cent, whereas China registered a meagre 31.25 per cent.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…The amount and quality of CSD in the developed countries is far better than the developing countries (Bhatia & Tuli, 2014; Wanderley, Lucian, Farache, & de Sousa Filho, 2008). In the race that features two of the fastest emerging economies, India is leading in CSD and China is lagging behind (Baskin, 2006; Bhatia & Tuli, 2014). Bhatia and Tuli (2014) found a significant difference in the extent of CSD between India and China; the total mean disclosure score of India was 81.34 per cent, whereas China registered a meagre 31.25 per cent.…”
Section: Resultsmentioning
confidence: 94%
“…In the race that features two of the fastest emerging economies, India is leading in CSD and China is lagging behind (Baskin, 2006; Bhatia & Tuli, 2014). Bhatia and Tuli (2014) found a significant difference in the extent of CSD between India and China; the total mean disclosure score of India was 81.34 per cent, whereas China registered a meagre 31.25 per cent. Alon, Latteman, Fetscherin, Li, & Schneider (2010) concluded that Indian firms disclose better than Chinese firms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although CSR in India has been favourably compared to that in other emerging economies [189,190], many have noted a continuing lack of priority of CSR issues in India despite the moves to mandatory disclosure [96,191]. Indian CSR reports have often contained little related to environmental issues [37,177,192].…”
Section: Discussionmentioning
confidence: 99%
“…Diversos estudos sobre divulgação ambiental e responsabilidade socioambiental já foram realizados no Brasil, referentes a vários setores e com os mais variados enfoques (OLIVEIRA; MACHADO;BEUREN, 2012;CRISÓSTOMO;PARENTE, 2012;MAZZA;OLIVEIRA, 2013;CABRAL;SANTOS;BRANDÃO, 2014). Há também várias pesquisas no exterior sobre divulgação ambiental e responsabilidade socioambiental, com enfoque e objeto de estudo variados (HA; KRISHNAN, 2011;SEN;MUKHERJEEE;PATTANAYAK, 2011;KUO;YEH;YU, 2012;CHANG, 2013;WANG;BERNELL, 2013;NORONHA;TOU;CYNTHIA;GUAN, 2013;PILLAY;BUYS, 2014;BHATIA;TULI, 2014;KUMAR;GUNASEKARAN;SINGH;PAPADOPOULOS;DUBEY, 2015;FIFKA;POBIZHAN, 2014;ZHANG;MOL;HE, 2016;MIDDLETON, 2015).…”
Section: Introductionunclassified